Optimizing Faculty Hiring in Higher Education Using Model Predictive Control - Bounkhel, Messaoud; Tadj, Lotfi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
As in any other sector, the objective of human resource manpower planning in academia is to avoid or to minimize a shortage or surplus of specific types of labor. In academia, the service offered is education, and the labor force is the lecturers and the professors. Hiring faculty members can have a positive socio-economic impact by improving education, driving innovation, supporting the local economy, and enhancing community development. Planning the manpower in academia is crucial for the future of the university. Our main tool is Model Predictive Control, which has received great interest during the last decades in the process industries, especially in chemical processes. Goodwin et al. (2001) report more than 2000 applications of Model Predictive Control. In this paper, we are using Model Predictive Control to obtain the optimal hiring rates for a university given its current and target faculty headcounts. A numerical example shows the effectiveness and the efficiency of the proposed method.